Substitution effect of fish meal with various plant protein sources on growth performance and feed utilization in rockfish (Sebastes schlegeli) diets including jack mackerel meal used as feed stimulants - Kim, June; Cho, Sung Hwoan (Frontiers in Marine Science, 2024)
Incorporating feed stimulants and attractants in low fish meal (FM) diets is a very effective way to improve palatability and increase feed intake and fish growth. This research aims to elucidate the substitution impact of different levels of FM with various plant proteins in diets with jack mackerel meal (JMM) inclusion as feed stimulants on the growth and feed utilization of rockfish (Sebastes schlegeli). A two-way (2 substitution levels [25% and 50%] × 3 substitution sources [corn gluten meal (CGM), soybean protein concentrate (SPC), and corn protein concentrate (CPC)]) ANOVA experimental design was adopted. In total, 525 fish averaging 8.3 g were assigned to 21 tanks (25 juvenile/tank). Seven isoprotetic and isolipidic feeds were formulated. The control (Con) diet contained 55% FM. CGM, SPC, and CPC were replaced for 25% and 50% FM in the Con diet, and then 22% JMM as feed stimulants was included at the cost of FM, named as the CGM25, CGM50, SPC25, SPC50, CPC25, and CPC50 diets, respectively. All diets were assigned to triplicate groups of rockfish. Rockfish were hand-fed to apparent satiation twice a day for 8 weeks. Rockfish fed the 25% FM substitution diets achieved superior (p < 0.0001 for both) weight gain and specific growth rate (SGR) compared to rockfish fed the 50% FM substitution diets, while rockfish fed the CGM-replaced diets achieved superior (p < 0.0001 for both) weight gain and SGR compared to rockfish fed the SPC- and CPC-replaced diets. The weight gain and SGR of rockfish fed the Con and CGM25 diets were superior to rockfish fed all other diets. Rockfish fed the 25% FM substitution diets achieved superior (p < 0.0001 for both) feed efficiency (FE) and protein efficiency ratio (PER) compared to rockfish fed the 50% FM substitution diets, while rockfish fed the CGM-replaced diets achieved superior FE and PER compared to rockfish fed the CPC-replaced diets. Rockfish fed the 25% FM substitution diets led to superior (p < 0.0001) protein retention (PR) compared to rockfish fed the 50% FM substitution diets. The biological indices, proximate composition, and amino acid profiles of the whole body, as well as the plasma and serum parameters of rockfish, were not changed by either substitution level or substitution source. In conclusion, the replacement of CGM for 25% FM in the rockfish diet with JMM inclusion can be made without deteriorating growth performance, feed consumption and utilization, biochemical composition, and plasma and serum parameters.